Strategi Marketing Melalui Celebrity Endorsement dan Influencer Marketing - Hardianawati (Jurnal Multidisiplin Madani, 2022)
Living in the digital era like today must make all companies aware that advertising effectively is no longer limited to TV, newspapers and billboards. The rise of the internet and social media shows promising business opportunities for the implementation of online advertising. Even advertising on digital platforms, such as social media using celebrity endorsers and influencer marketing, can be one of the latest alternatives to get attention and awareness from the public considering that there are 174 million internet users in Indonesia. They also access the internet on average more than 4 hours per day via cell phones. And 3 hours 46 minutes are used to access social media according to We Are Social and Hootsuite 2020 data. The purpose of this study is to explain which digital platform is more effective in carrying out marketing strategies, whether using celebrity endorsement or influencer marketing. This research uses literature study method in collecting the data. The data in this study used secondary data collected from information on articles, books and journals. The result is which marketing strategy is most effective depends on the marketing objectives. If you want to reach a wider audience and increase brand awareness quickly, and form a brand image to make it more classy, ​​it is better to use a celebrity endorsement strategy. However, if you want to reach a more specific audience and build audience trust in the brand through real and authentic content, it is more appropriate to use an influencer marketing strategy.